Madagascar : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
This paper analyzes the recent economic developments in Madagascar under the new Poverty Reduction and Growth Facility Arrangement. It highlights the production, income, and overall fiscal developments; discusses various measures to simplify the tax system, improve tax and customs administration; and tighten the expenditure management of the country. The paper provides a detailed study of the monetary developments, structure of the financial sector, balance of payments, external debt, and structural reforms of the country.